Imprint of ancestral and modern threats in human mind - experience of fear, disgust, and anger - Landová, Eva; Polák, Jakub; Janovcová, Markéta; Štolhoferová, Iveta; Peterková, Šárka; Chomik, Aleksandra; Frynta, Daniel (Frontiers in psychology, 2024)
INTRODUCTION: Threats to our survival are often posed by the environment in which humans have evolved or live today. Animal and human ancestors developed complex physiological and behavioral response systems to cope with two types of threats: immediate physical harm from predators or conspecifics, triggering fear, and the risk of infections from parasites and pathogens leading to the evolution of the behavioral immune system (BIS) with disgust as the key emotion. Here we ask whether the BIS has adapted to protect us from pandemic risks or poisoning by modern toxic substances. METHODS: We have developed a survey comprised of 60 vignettes describing threats evoking fear and disgust belonging to one of the three main categories of threats: (1) ancestral, (2) modern, and (3) pandemic of airborne disease. Each vignette was evaluated on a 7-point Likert scale based on fear, disgust, and anger. Respondents also completed an assessment battery. RESULTS: The results show that the strongest fear is triggered by modern threats (electricity, car accidents), while the highest disgust is evoked by ancient threats (body waste products, worms). Disgust does not respond to modern threat stimuli such as toxic substances or radioactivity as these evoke mainly fear and anger. A discriminant factor analysis classified nine out of 10 pandemic disgust vignettes into the ancestral disgust category, convincingly assigning the pandemic disgust threats to the ancestral type. Gender, age, and type of education were significant moderators of emotional responses across all threat categories. DISCUSSION: Our study reveals that while fear is more context-dependent, particularly triggered by modern threats, disgust operates on an evolutionarily hardwired basis, making it less effective against contemporary risks. Furthermore, disgust experienced during a pandemic outbreak is more closely aligned with ancestral disgust-related threats tapping into evolutionary ancient survival circuits of the BIS. However, as disgust declines with age, the brain must adaptatively shift the emotional processing from disgust to fear to protect older adults from contamination risks. Finally, our study reveals that pandemic fear is better predicted by specific behaviors rather than general anxiety, suggesting a need for new assessments.
Keywords: fear module; COVID-19; pandemic; evolutionary psychology; behavioral immune system